Perkawinan Eksogami dan Dampaknya dalam Sejarah Bali Kuna (Sebuah Studi Kasus) - I Made Jaya (Balai Arkeologi Yogyakarta, 1994)
This article will discuss exogamous marriage in the case study of Gunapriyadharmapatni and Dharma Udayana Warmadewa. It is consider as exogamous marriage because Gunapriyadharmapatni whose first name is Mahendradata comes from the clan/lsana dynasty (East Java), while Dharma Udayana Warmadewa comes from the clan/Warmadewa dynasty in Bali. In ancient history it was stated that the marriage of Gunapriyadharmapatni and Dharma Udayana Warmadewa had three sons, Erlangga, Marakata, and Anak Wungsu. Thus, their sons held reign of monarchy in Old Bali era (heirs). The data sources used in this article are inscriptions published around the X-IX CE, as well as several ancient manuscripts such as Negarakertagama, Pararaton, and Calon Arang.